UJI KUAT TEKAN BETON DAN UJI KUAT TARIK BAJA TULANGAN PROYEK PEMBANGUNAN CITIMALL GARUT - Alfandi, Alif; -, Sutrisno (Jurnal Mahasiswa Terapan; Vol 1 No 2 (2025): Jurnal Mahasiswa Terapan, 2025)
The purpose of this study was to analyze the compressive strength of concrete, the tensile strength of reinforcing steel used in the Citimall Garut construction project and calculate the load of the Citimall Garut building, and compare the results of the concrete compressive strength test with SNI 1974-2011 and the tensile strength of reinforcing steel with SNI 2052:2017. Based on the analysis of the building load calculation of 261,754.979 Kg or 261.754 Tons. Based on the results of the concrete compressive strength analysis above, seen from SNI 2847-2013, the test results on 28-day-old concrete were 314.832 Kg/cm2 or 30.85 MPa. Based on these results, the compressive strength value exceeds the planned compressive strength value, namely K 300 or 29.4 MPa. From the results above, it can be concluded that the mix design that has been carried out is in accordance with the target and can be used for the construction of the Citimall Garut project. Based on the analysis of the tensile strength test of reinforcing steel above, seen from SNI 2052-2017, the results of the examination of the size of the threaded/finned reinforcing steel (BJTS) test samples used in the study, of the five samples used, all of them were not suitable. However, the results of the mechanical properties examination of the threaded/finned reinforcing steel (BJTS) samples used in the study, from the five samples, are in accordance with SNI 2052-2017.